An Analysis of Denotation and Connotation in Chairil Anwar’s Poem - Zuhdah, Daumi Rahmatika; Alfain, Shinta Nuriya (e-Journal of Linguistics; Vol 14 No 1 (2020): e-jl JanuaryDO - 10.24843/e-jl.2020.v14.i01.p11, 2020)
This study primarily investigates denotative and connotative meaning in words. Both of denotation and connotation are helpful for readers of poetry to find the interpretations and implied meaning. This analysis focuses on meaning of words that was taken randomly from a poem. The data is analyzed descriptively using Griffith’s concept about three stages of interpretation, there are literal meaning, explicature and implicature. The result shows that a word not only has denotation, but also negative and positive connotation. Both of negative and positive connotations are possible that refer to an expression or a word. The major finding of the study is every word has one connotative meaning either negative or positive.